Measuring Racial Discrimination with Fair Housing Audits: Caught in the Act - Yinger, John (American Economic Review, 1986)
A survey technique called a fair housing audit provides a direct measure of racial discrimination in housing and an opportunity to test hypotheses about its causes. Audits conducted in Boston in 1981 uncovered extensive discrimination; black housing seekers were told about 30 percent fewer available housing units than were whites. This paper finds that the primary cause of this discrimination is economic: Housing agents cater to the racial prejudice of current or potential white customers.